2019
DOI: 10.1038/s41418-019-0423-5
|View full text |Cite|
|
Sign up to set email alerts
|

Splicing factor derived circular RNA circUHRF1 accelerates oral squamous cell carcinoma tumorigenesis via feedback loop

Abstract: Emerging evidences have suggested the vital roles of circular RNA (circRNA) in the human cancers. However, the underlying biological functions and biogenesis of circRNA in the oral squamous cell carcinoma (OSCC) is still ambiguous. Here, we investigate the oncogenic roles and biogenesis of the novel identified circRNA, circUHRF1 (hsa_circ_0002185), in the OSCC tumorigenesis. Results showed that circUHRF1 was markedly upregulated in the OSCC cells and tissue, besides, the overexpression was closely correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 41 publications
1
130
0
Order By: Relevance
“…CircIRAK3 is increased in metastatic BC cells and predictive recurrence, constructing the circIRAK3/miR-3607/FOXC1/IRAK3 positive-feedback loop 25 . The generated circRNAs are distributed both in cytoplasm and nucleus, and the subcellular distribution determines the functions of circRNAs 26 . The cytoplasmic circRNA could target the miRNA, acting as miRNA sponge, to indirectly regulate the functional proteins.…”
Section: Discussionmentioning
confidence: 99%
“…CircIRAK3 is increased in metastatic BC cells and predictive recurrence, constructing the circIRAK3/miR-3607/FOXC1/IRAK3 positive-feedback loop 25 . The generated circRNAs are distributed both in cytoplasm and nucleus, and the subcellular distribution determines the functions of circRNAs 26 . The cytoplasmic circRNA could target the miRNA, acting as miRNA sponge, to indirectly regulate the functional proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The in silico analyses were complemented by functional characterization of a novel, pro-tumorigenic circRNA, named circFLNB, thus substantiating the tumorigenic role of the OSCC-associated circRNAome. Lending further support to this notion, a recent study has also discovered an OSCC-associated, splicing factor-derived circRNA, named circUHRF1, and demonstrated its involvement in tumorigenesis [30]. Interestingly, a circRNA (circFLNA) derived from another filamin family gene, filamin A, was reported to impact the migration of the laryngeal squamous cell carcinoma, which is related histologically and anatomically to oral cancer [31].…”
Section: Discussionmentioning
confidence: 86%
“…By gain-and loss-functional experiments, we further found that overexpression of circ_0000199 was able to promote cell proliferation and inhibit apoptosis, while knockdown of circ_0000199 exhibited opposite effects. Previous studies have shown that circRNAs, as a new type of competitive endogenous RNA (ceRNA), act as miRNA sponge by which interact with miRNA to cause dysregulated expression of miRNA target genes, thereby participating in OSCC process 25,26 . In this study, bioinformatics software predicted that circ_0000199 could interact with miR-145-5p and miR-29b-3p, which were downregulated in OSCC cells.…”
Section: Discussionmentioning
confidence: 99%